Diffusion kurtosis imaging of the liver at 3 Tesla: in vivo comparison to standard diffusion-weighted imaging - Budjan, Johannes; Lassel, Elke Angelika; Zöllner, Frank G.; Lemke, Andreas; Wambsganß, Jens; Schönberg, Stefan; Attenberger, Ulrike (Acta radiologica, 2018)
Background Functional techniques like diffusion-weighted imaging (DWI) are gaining more and more importance in liver magnetic resonance imaging (MRI). Diffusion kurtosis imaging (DKI) is an advanced technique that might help to overcome current limitations of DWI.PurposeTo evaluate DKI for the differentiation of hepatic lesions in comparison to conventional DWI at 3 Tesla.Material and MethodsFifty-six consecutive patients were examined using a routine abdominal MR protocol at 3 Tesla which included DWI with b-values of 50, 400, 800, and 1000?s/mm2. Apparent diffusion coefficient maps were calculated applying a standard mono-exponential fit, while a non-Gaussian kurtosis fit was used to obtain DKI maps. ADC as well as Kurtosis-corrected diffusion (D) values were quantified by region of interest analysis and compared between lesions.ResultsSixty-eight hepatic lesions (hepatocellular carcinoma [HCC] [n?=?25]; hepatic adenoma [n?=?4], cysts [n?=?18]; hepatic hemangioma [HH] [n?=?18]; and focal nodular hyperplasia [n?=?3]) were identified. Differentiation of malignant and benign lesions was possible based on both DWI ADC as well as DKI D-values (P values were in the range of 0.04 to?
First published online: April 28, 2017
Gesehen am 21.08.2018